Bioenergy, food security and poverty reduction: Mitigating tradeoffs and promoting synergies along the Water-Energy-Food Security Nexus - Alisher Mirzabaev; Dawit Guta; Jann Goedecke; Varun Gaur; Jan Börner; Detlef Virchow; Manfred Denich; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2014)
Modern bioenergy is a core ingredient of sustainable economic development as it plays an important role in poverty reduction and green growth. This makes bioenergy innovations critical, especially in developing countries where many households and rural communities rely on traditional bioenergy. Managing the multiple tradeoffs among bioenergy use, agricultural productivity, and ecosystem functions is a major development challenge. Addressing this challenge requires the identification of the drivers, tradeoffs and impacts of bioenergy production, trade and use in the Water, Energy and Food Security Nexus. The key objective of this paper is to provide an analytical framework and assess the track record of policy actions to stimulate modern bioenergy innovation in order to achieve multiple-win outcomes in terms of poverty alleviation, improved health and gender empowerment and environmental sustainability. We begin by describing the global trends and drivers in bioenergy production, trade and use. Secondly, we review the state of the art on impacts and links of bioenergy with the other Nexus components. Thirdly, we suggest a conceptual framework for evaluating the synergies and tradeoffs of bioenergy with other bioeconomic and economic activities along the Nexus. Follow-up empirical research at household and community levels in several developing countries will be based on this framework. Finally, a discussion on the conceptual framework is enriched by insights on the relevant actors, the tools and mechanisms specific to these actors for catalyzing innovations in the bioenergy for development.
Keywords: 330; bioenergy; poverty reduction; food security; decentralized energy; WEF Nexus tradeoffs and synergies; households and communities; innovations